Downregulation of tumor-suppressor gene LHX6 in cancer: a systematic review - Nathalia Evelyn; Theardy Madelaine Skolastika; Elvira Sharleen; Rosellinny Graciella; Liyanto Andrew Steven; Utama Michael Putra; Sumarpo Anton (Sciendo, 2018)
Introduction. LIM Homeobox 6 (LHX6) encodes a LIM homeodomain transcription factor, contributes to tissue development and morphogenesis, and is mostly expressed in medial ganglionic eminence and odontogenic mesenchyme. However, it has been reported to play a role in cancer progression. This narrative review summarizes literatures that emphasize the molecular regulation of LHX6 in tumorigenesis.